ACEHNESE ONOMATOPOEIAS: INVESTIGATING, LISTING, AND INTERPRETING THEIR MEANINGS - Ida Muliawati; Dara Yusnida (Englisia: Journal of Language, Education, and Humanities, 2019)
Sound-imitating words, called onomatopoeia, presents in most of languages in the world including Acehnese language, one of traditional languages in Indonesia, in which a great deal of onomatopoeias exist in it due to its unique constructions of onomatopoeia. This research aims at finding out kinds of Acehnese onomatopoeias understood and spoken among native Acehnese people by using Pidie dialect. Thus, five people in the Pidie Jaya regency were sorted out to be the subject informants by actualizing purposive and snowball technique. Moreover, a descriptive qualitative method was manifested in the research by actualizing some instruments to get the data such as structured interviewing and documentation. Hence, all of the data were interpreted in words by listing, transcribing their phonetics orderly, as well as describing both their function and meaning. A three-step analysis – data reduction, data verification, and data display-- was employed to describe the data gathered.  Result of the research reveals that Acehnese Onomatopoeias covers a wide range of expressions in sound-imitating words which are categorized into three big classes; Phonomimes which includes auditory impressions of various imitative sounds of nature; Phenomimes -- mimetic words to describe objects’ condition and human’s activities; and Psychomimes – symbolizing psychological state or inner feelings. Still, most of Acehnese onomatopeic words are in forms of repetition and nasalization which seems to be more unique compared to other languages.